EzPreemie study protocol: a randomised controlled factorial trial testing web-based parent training and coaching with parents of children born very preterm. Issue 6 (22nd June 2022) - Greene, Michelle M; Schoeny, M E; Berteletti, Julia; Keim, Sarah A; Neel, Mary Lauren; Patra, Kousiki; Smoske, Shea; Breitenstein, Susan
Abstract : Introduction: Children born very preterm (VPT; gestational age <32 weeks) are twice as likely to demonstrate behaviour problems such as aggression, non-compliance, temper tantrums and irritability compared with their term-born peers. While behavioural parent training (BPT), also referred to as behaviour therapy is a gold standard for prevention and treatment of childhood problem behaviours, there are limited accessible and effective BPT interventions for families with children born VPT. The purpose of this paper is to describe a multicentre, randomised controlled protocol for a factorial design trial evaluating the independent and combined effects of the ez Parent BPT intervention plus brief, weekly coaching calls on parent and child outcomes for families with toddlers born VPT. Methods and analysis: The study employs a 2×2 factorial randomised design. Parents (n=220) of children aged 20–30 months corrected age who were born VPT (<32 weeks) will be recruited from two large metropolitan Neonatal Intensive Care Units follow-up clinics and randomised to one of four conditions: (1) ez Parent (2) ez Parent +coach, (3) Active control or (4) Active Control +coach. Data on parenting and child behaviour outcomes will be obtained from all participants at baseline and 3, 6 and 12 months postbaseline. All analyses will use an intention-to-treat approach, independent of their actual dose of each intervention. Ethics and dissemination: The study protocol has been approved by The Ohio State University Institutional Review Board (IRB) using a single IRB. Study results will be disseminated through presentations at regional and national conferences, publications in peer-reviewed journals, and sharing research reports with participating families and recruiting sites. Trial registration number: NCT05217615 .